1977
DOI: 10.1097/00004032-197709000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Inhaled Radioactive Particles by Lung Lavage - A Review

Abstract: Lung lavage effectively removed inhaled radioactive particles from the lungs in a variety of animal experiments. Several types of lung lavage procedures were used. The removal of several different radionuclides has been studied, including 9sZr-Y5Nb, '44Ce, 239Pu, 23aPu and 24'Am. A single lung lavage in a beagle dog removed about 12% of the initial lung burden (ILB) of the inhaled material. Multiple lung lavages have removed up to 50% of the ILB. A single lung lavage in beagle dogs performed between 2 and 196 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…For lung intakes of insoluble particles with a high activity radionuclide ( 192 Ir, 90 Sr, 210 Po), one should consider physical removal by bronchioalveolar lavage (BAL). In addition to being used as a diagnostic procedure for radiation pneumonitis and other lung diseases, BAL is used therapeutically to remove unwanted material, including insoluble radionuclides, from the lungs of adults and children [14][15][16][17]. It should be performed by only an experienced health care provider, typically a pulmonologist or thoracic surgeon.…”
Section: Physical Removal Of Radionuclidesmentioning
confidence: 99%
“…For lung intakes of insoluble particles with a high activity radionuclide ( 192 Ir, 90 Sr, 210 Po), one should consider physical removal by bronchioalveolar lavage (BAL). In addition to being used as a diagnostic procedure for radiation pneumonitis and other lung diseases, BAL is used therapeutically to remove unwanted material, including insoluble radionuclides, from the lungs of adults and children [14][15][16][17]. It should be performed by only an experienced health care provider, typically a pulmonologist or thoracic surgeon.…”
Section: Physical Removal Of Radionuclidesmentioning
confidence: 99%
“…The only other approach to eliminate high activity MOX particles would be to use bronchopulmonary lavage. The use of this technique as a countermeasure for lung contamination with insoluble actinides has been addressed over the years in experimental models (see Muggenburg et al, 1977;Nolibé et al, 1989;National Council on Radiological Protection and Measurements. (NCRP), 2009).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…As early as 1963, RAMIREZ et al [3) reported on whole lung lavage (WLL) using a large volume of fluid in patients with pulmonary alveolar proteinosis. Since then, this technique has been proposed for removal of any alveolar filling material, in conditions such as alveolar protein os is [ 4,5], alveolar microlithiasis (6], acute silicosis [7], or accidental inhalation of radioactive particles (8,9). Its use has also been proposed in obstructive lung diseases [10], to remove the mucous secretions accumulated in the bronchial tree, as in asthma [11,12], or cystic fibrosis (13,14).…”
Section: Therapeutic Applications Of Bronchoalveolar Lavagementioning
confidence: 99%
“…The benefit of WLL in human contamination is not yet clearly defined [8,9]. Experimental studies on dogs and baboons have been carried out over the last 20 yrs to determine the efficacy of WLL in the removal of such particles.…”
Section: Inhalation Of Radioactive Particlesmentioning
confidence: 99%